On structure of branched continued fractions - Antonova, T.M. (Carpathian Mathematical Publications, 2024)
The paper provides a survey of various multidimensional generalizations of continued fractions that arose when solving the problem of approximating functions of one or several variables, including some hypergeometric functions. It is shown that all these generalizations can be considered as separate cases of the general concept of a branched continued fraction, the definition of which is given in the work.